As mulheres vão à luta: experiência e resistência da paraibana Maria da Penha Nascimento Silva (1970-1991) - Silva, Janaína Vicente da (2022)
The present dissertation has as a main objective to analyse the experiences of resistance in the ‘1Brejo Paraibano’ with a perspective of female protagonism, specially about the unionist Maria da Penha Nascimento Silva (1949-1991), emphasizing her struggle for the labor rights and gender equality, during the resistance movements in Paraiba, between 1970 and 1991. In the 1980s, Penha, with other women from ‘Brejo’ created two women’s movements, MMT/PB (2Movimento de Mulheres Trabalhadoras do Brejo Paraibano) and MMB (3Movimento de Mulheres do Brejo.), with the aim of aware her fellow activists of their rights as women and workers. The theoretical fundaments is supported by Salvatici (2005), Pollak (1989), Perrot (1991, 2006), Rago (1995, 2001, 2012, 2014), Thompson (1981, 2001, 2002), Souza (2019) and others referenced. Based on bibliographical research, semi-structured interviews, informal conversations and analysis of documents (booklets, reports, photos and Maria da Penha's books), our narrative was structured around the struggle experience of the working class and the arising of Penha as a leader in Brejo. Using concepts like memory, resistance, patriarchal society, class struggle and gender, we seek to (re)build the memory of women who fought for gender equality inside of the struggle movements for better working conditions, starting in the life experience of (4paraibana) Maria da Penha. This work hopes not only contributes for a more comprehensive view of History, because for a long time women were in historiographical invisibility, but also reinforce the female protagonism in union organization, recognizing the multiplicity and diversity of actions present in the women and men’s struggles in social movements of countryside and city.